2010
DOI: 10.1016/j.molcel.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Attenuates Smad-Mediated Transcription

Abstract: The versatile cytokine transforming growth factor β (TGF-β) regulates cellular growth, differentiation, and migration during embryonic development and adult tissue homeostasis. Activation of TGF-β receptors leads to phosphorylation of Smad2 and Smad3, which oligomerize with Smad4 and accumulate in the nucleus where they recognize gene regulatory regions and orchestrate transcription. Termination of Smad-activated transcription involves Smad dephosphorylation, nuclear export, or ubiquitin-mediated degradation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 26 publications
(40 reference statements)
8
125
0
1
Order By: Relevance
“…38 As another typical example, PARP1 can dissociate Smad complexes from DNA through poly(ADP-ribosyl)ating Smad3 and Smad4, therefore attenuating Smad-mediated transcription and inhibiting TGF-β-induced epithelial-mesenchymal transition (EMT). 39 Since we have demonstrated before the function of Snail-LSD1 on E-cadherin suppression and EMT induction, there is also a possibility that PARP1 participates in this regulation process. In contrast to the Smad-PARP1 model, however, poly(ADP-ribosyl)ation of Snail by PARP1 would rather enhance the inhibitory effect of Snail-LSD1 on E-cadherin and promote EMT.…”
Section: Discussionmentioning
confidence: 89%
“…38 As another typical example, PARP1 can dissociate Smad complexes from DNA through poly(ADP-ribosyl)ating Smad3 and Smad4, therefore attenuating Smad-mediated transcription and inhibiting TGF-β-induced epithelial-mesenchymal transition (EMT). 39 Since we have demonstrated before the function of Snail-LSD1 on E-cadherin suppression and EMT induction, there is also a possibility that PARP1 participates in this regulation process. In contrast to the Smad-PARP1 model, however, poly(ADP-ribosyl)ation of Snail by PARP1 would rather enhance the inhibitory effect of Snail-LSD1 on E-cadherin and promote EMT.…”
Section: Discussionmentioning
confidence: 89%
“…As an increasing number of studies have shown, PAR can be accumulated in normal, steady-state, or basal conditions (e.g., during hormonal signaling, certain stages of development, circadian clock function, and mitosis) without triggering stress responses (Tulin and Spradling 2003;Bai et al 2007;Chang et al 2009;Asher et al 2010;Lonn et al 2010;Geistrikh et al 2011;Rouleau et al 2011;Yoo et al 2011;Erener et al 2012). How does the cell interpret PAR accumulation as a stress signal in one circumstance, but not another?…”
Section: Parp-and Par-dependent Processes In Normal Conditions?mentioning
confidence: 99%
“…It was proposed that acetylation of Lys19 in SMAD2Dexon3 promotes DNA binding by releasing the MH1 domain from this inhibitory interaction. Another posttranslational modification that regulates DNA binding of SMAD3 -SMAD4 complexes is poly-ADP-ribosylation (PARylation), which is induced by poly(ADP-ribose) polymerase-1 (PARP1) (Lönn et al 2010). Both SMAD3 and SMAD4 were found to be PARylated, and in SMAD3, the sites of PARylation were mapped to Glu50 and Glu52 in the MH1 domain.…”
Section: Dna Binding Of Smad Complexes and Its Regulation By Posttranmentioning
confidence: 99%